A pillar[5]arene-based and OH− dependent dual-channel supramolecular chemosensor for recyclable CO2 gas detection: High sensitive and selective off-on-off response. (March 2020) - Zhu, Wen-Bo; Wei, Tai-bao; Fan, Yan-Qing; Qu, Wen-Juan; Zhu, Wei; Ma, Xiao-Qiang; Yao, Hong; Zhang, You-Ming; Lin, Qi
Abstract: A novel supramolecular chemosensor (PNG ) was successfully constructed by 5-(3-nitrophenyl)-furfural-functionalized Pillar[5]arene(PN ) and bipyridine salt(G ) via exo-wall π…π interactions. Interestingly, the chemosensor PNG could detect OH − and CO2 with high selectivity, sensitivity and excellent recyclable properties. The fluorescent detection limits of PNG for OH − and CO2 are 2.03 × 10 −8  M and 9.1 × 10 −8  M (2.22 ppm), respectively. The colorimetric detection limits for OH − and CO2 are 3.78 × 10 −8  M and 1.13 × 10 −7  M (2.76 ppm), respectively. This study is simple and effective for OH − and CO2 detection, and provides supramolecular fields with potential practical application in anion and gas detection. Graphical abstract: Image 1 Highlights: Synthesis of a novel arylfurfural functionalized pillar [5]arene (PN ). The PN and G could self-assemble to supramolecular chemosensor PNG by exo-wall π…π interactions. The PNG shows excellent recyclable dual-channel detections for OH − and CO2 . PNG -based sequential detection for OH − and CO2 with high sensitivity and selectivity.